2005
DOI: 10.1007/s10456-005-3588-0
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole Inhibits Angiogenesis in vitro and Tumor Growth in vivo

Abstract: Copyright: Ciccone et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License 3.0 (CC BY 3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. ABSTRACT Nitric oxide (NO) exerts conflicting effect on tumor growth and progression, depending on its concentration. We aimed to characterize the anti-cancer activity of a new NO donor, Ni(SalPipNONO) belonging to the class of metal-non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…However, 2-ME had previously shown low inhibition at 10 μM and moderate inhibition at 50 μM (Kang et al, 2006), whereas our assay showed low and moderate inhibition at 0.01–0.2 and 1 μM, respectively. Moreover, compared to the method by Friis et al (2003, 2005), which is a similar assay to ours, levamisole was reported to have mild inhibition at 500 μM (in our study 0.01–1 μM), moderate at 750–1000 μM (in our study 100–500 μM), and strong at 2000 μM (in our study 1000–2000 μM). The anti-VEGF was reported to have moderate to strong inhibition at 0.1–10 mg/ml in an in vitro model with different study setup (Sims et al, 2008) compared to our assay (inhibition at 0.5–50 μg/ml).…”
Section: Discussionsupporting
confidence: 88%
“…However, 2-ME had previously shown low inhibition at 10 μM and moderate inhibition at 50 μM (Kang et al, 2006), whereas our assay showed low and moderate inhibition at 0.01–0.2 and 1 μM, respectively. Moreover, compared to the method by Friis et al (2003, 2005), which is a similar assay to ours, levamisole was reported to have mild inhibition at 500 μM (in our study 0.01–1 μM), moderate at 750–1000 μM (in our study 100–500 μM), and strong at 2000 μM (in our study 1000–2000 μM). The anti-VEGF was reported to have moderate to strong inhibition at 0.1–10 mg/ml in an in vitro model with different study setup (Sims et al, 2008) compared to our assay (inhibition at 0.5–50 μg/ml).…”
Section: Discussionsupporting
confidence: 88%
“…Notably, this effect is identical to what is observed in the assay when VEGF is omitted from the growth medium [37], [38], which may indicate that N -methyllevamisole triflate ( 7a ) effectively interferes with VEGF signalling, albeit at relatively high concentrations. Though, based on this preliminary test, we cannot rule out possible interaction of these chemotypes with other phosphatases and/or kinases.…”
Section: Resultssupporting
confidence: 67%
“…Likewise the anthelminthic drug ( S )-levamisole hydrochloride (Ergamisol ® ; 1 ) [29], [30], which has also been used in the treatment of rheumatoid arthritis [31], [32], as well as an immunostimulant adjuvant in chemotherapy for several types of cancer [33][36], was recently shown to exhibit angiogenesis inhibitory activity in vitro and tumor growth inhibition in vivo [37], [38]. The in vitro antiangiogenic effect resembled that of Avastin in several respects, but especially with regard to inhibition of network formation and induction of non-differentiated clusters of cells [38].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that it affects cell proliferation in different cancers [15] and modulates the phosphorylation relevant for both cell cycle progression and apoptosis. Studies have also shown that it can be used for anti- helminthic infestations and various autoimmune diseases [16], [17]. Besides, it has been shown that levamisole has anticancer activity in combination with fluorouracil (5-FU) as adjuvant therapy for tumor-node-metastasis (TNM) stage III (Dukes' C) colon carcinoma [18].…”
Section: Introductionmentioning
confidence: 99%